"The book of tribulations": the Syrian Muslim apocalyptic tradition - Nuʿaim Ibn-Ḥammād al-H̱uzāʿī -844 (Edinburgh studies in Islamic apocalypticism and eschatology, 2017)
The Book of Tribulations is the earliest complete Muslim apocalyptic text to survive, and as such has considerable value as a primary text. It is unique in its importance for Islamic history: focusing upon the central Syrian city of Hims, it gives us a picture of the personalities of the city, the tribal conflicts within, the tensions between the proto-Muslim community and the majority Christian population, and above all details about the wars with the Byzantines. Additionally, Nu`ʻaym gives us a range of both the Umayyad and the ʻAbbāsid official propaganda, which was couched in apocalyptic and messianic terms